Efficacy and safety of laparoscopy versus local injection with absolute ethanol in the management of tubal ectopic pregnancy - Yin Bi; Yuanping She; Zhengping Tian; Zhiyao Wei; Qiuyan Huang; Shengbin Liao; Yuan Ye; Aiping Qin; Yihua Yang (Elsevier, 2019)
Objective: To compare the efficacy and safety between laparoscopy and local injection with absolute ethanol (AE) for treating tubal ectopic pregnancy (EP). Study design: Retrospective cohort study of ectopic pregnancies in the fallopian tube from two tertiary hospitals between January 2015 and December 2017. Clinical information such as presenting symptoms, reproductive history, possible risk factors, initial diagnosis, serum beta-human chor-ionic gonadotropin (β-HCG) level, transvaginal ultrasonography findings, methods of treatment and outcomes were reviewed and analyzed. Results: A total of 119 patients were identified for this study. The diagnosis was based on clinical manifestations, ultrasonography scan and dynamic serum β-HCG. 71.4% of women (85/119) had at least one risk factor for ectopic pregnancy, with the most common risk factors being a history of induced labor, uterine curettage, spontaneous abortion or tubal pregnancy. 64 patients were managed by laparoscopic surgery (Group A) and 2 subjects were failure and followed by a systemic methotrexate (MTX) prescription. The other 55 patients had local injection with absolute ethanol, of which 9 cases failed, followed by a second local injection and intramuscular MTX. The HCG decrease rate post absolute ethanol injection was a value predictive factor for prognosis. Moreover, the pregnancy rate one-year post treatment in local injection subjects (10/55, 18.2%) was higher than that of surgical subjects (5/64, 7.8%). Conclusion: Local injection of absolute ethanol and laparoscopic surgery for tubal ectopic pregnancy are both effective and relatively safe, but laparoscopic surgery has better efficacy and shorten hospitalization day. Local injection may be less invasiveness and thus beneficial to fertility preservation. Keywords: Tubal ectopic pregnancy, Laparoscopic surgery, Local injection